A 2D Model Which Accounts for Transverse Strains in a Linear Elastic Thick Shell. (18th October 2022) - Robert, Nzengwa; Landry, Djopkop Kouanang; Merlin, Bodol Momha; Chills, Amba Jean; Joseph, Nkongho Anyi; Ambassa, Zoa
Abstract : In this paper we present a 2D four-parameter model that accounts for the variation of transverse deformation through-the-thickness in thick linear elastic shells. This model is deduced directly from the 3D elasticity equations of the traction-displacement boundary value problem. Transverse shear strains and thickness variation are accountable through additional terms which appear in the final equations besides well-known terms in the classical Kirchhoff-Love models for thin shells. A unique solution of the variational equation is established, and numerical and analytical results are compared with satisfaction.